2007
DOI: 10.1111/j.1445-2197.2007.04296.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality‐of‐life Effect of Tonsillectomy in a Young Adult Group

Abstract: Tonsillectomy in a young adult group results in significant improvement in overall quality of life, physical health and general well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 13 publications
3
21
1
1
Order By: Relevance
“…All eight studies reported a general improvement in QoL after tonsillectomy in adults (Table II). [4][5][6][7][8][9][10][11] Several studies had a relatively low response rate, below 50 per cent. 4,[6][7][8] This could possibly have contributed to a selection bias, since patients with an improvement in their QoL may be more likely to respond.…”
Section: Generalmentioning
confidence: 99%
See 3 more Smart Citations
“…All eight studies reported a general improvement in QoL after tonsillectomy in adults (Table II). [4][5][6][7][8][9][10][11] Several studies had a relatively low response rate, below 50 per cent. 4,[6][7][8] This could possibly have contributed to a selection bias, since patients with an improvement in their QoL may be more likely to respond.…”
Section: Generalmentioning
confidence: 99%
“…15-25 years). 8 This potentially allowed these authors to make specific observations on that particular age group. Agreeing with Baumann et al, and in contrast with Bhattacharya et al, Richard and colleagues' social functioning subscale results indicated a non-significant change, and thus the possibility of no social benefit from tonsillectomy.…”
Section: Studies Using the Glasgow Benefit Inventorymentioning
confidence: 99%
See 2 more Smart Citations
“…Our response rate of 48.8% should be considered when examining how potential biases may have led to greater than true improvements in the scores of the questionnaires used. However, this response rate is higher when compared with similar QoL and by mail survey conducted studies, which mention rates ranging from 30-38.5% [26][27][28][29]. Also of note is that patients with CRS were not categorised into groups with respect to the presence or absence of nasal polyps or aspirin intolerance, which was not an exclusion criterion.…”
Section: Discussionmentioning
confidence: 86%